Synthesis, chemical reactivity and biological evaluation of the novel 2-[(1-chloro-3-oxoprop-1-en-1-yl)amino]-4-(4-methoxyphenyl)-6-oxo-1, 6-dihydropyrimidine-5-carbonitrile. Issue 19 (2nd October 2021) - Farouk, Osama; Ibrahim, Magdy A.; El-Gohary, Nasser M.
Abstract: Acetylation of 2-amino-4-(4-methoxyphenyl)-6-oxo-1, 6-dihydropyrimidine-5-carbonitrile (2 ) using acetic anhydride afforded N -pyrimidinylacetamide derivative 3 which upon formylation using Vilsmeier-Haack reagent produced β-chloroenaldehyde derivative 4 . The chemical behavior of compound 4 was investigated toward some primary amines as well as heterocyclic amines yielding the corresponding Schiff bases. Compound 4 is used as a building block for the construction of nitrogen heterocyclic compounds such as pyrazoles, pyrimidines, pyridopyrimidine and diazepine through its reaction with a diversity of bifunctional nucleophiles such as hydrazines, guanidines, 6-aminouracil and ethylenediamine. The biological activity of the synthesized compounds was investigated. Structures of the newly synthesized products were deduced on the basis of their analytical and spectral data. Graphical Abstract: UF0001